PENCEGAHAN DAN PENANGGULANGAN TRANSMISI COVID-19 BERBASIS PEMBERDAYAAN MASYARAKAT DI KELURAHAN GERGUNUNG KLATEN UTARA - Rr.Vita Nur Latif; Dyah Rahmawatie Ratna Budi Utami; Rahmawati Rahmawati; Ronald Barung; Akhmad Azmiardi; Anita Lufianti; Dipo Wicaksono Kamal; Farid Setyo Nugroho; Ida Nursanti; Sri Mulyanti (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic is still a volatile and unpredictable condition that has an impact on all aspects of life. Government programs such as lockdown, health protocols and vaccinations, as well as local wisdom such as jogo tonggo are alternative options in controlling Covid-19. The limited understanding and behavior of the community raises the issue of stigma on survivors and can affect the ineffectiveness of jogo tonggo, as well as post-vaccination wrong behavior. The purpose of this program is to the transmission of COVID-19 through reducing stigma, increasing post-vaccination knowledge and strengthening the community-based jogo tonggo program in the Gergunung. The implementation method uses a Problem Solving Cycle approach with advocacy strategies, atmosphere building and community empowerment movements. The targets of this activity include the head of the Covid-19 task force who is also the head of the RW in the Gergunung Village area, through the Trainning of Trainee (TOT) activities to prevent and control the transmission of Covid-19. The results show that 100% of Jogo Tonggo posts have been formed in 13 RW areas of Gergunung Village. Knowledge showed no significant changes. There are 3 video and pocket book as a medium of education for the Gergunung community